Johann Gottlieb Georgi or Peter Simon Pallas: review regarding the authorship and description of Lacerta taurica (Squamata, Lacertidae) - Kukushkin, Oleg; Tillack, Frank; Doronin, Igor; Kluge, Nikita; Jablonski, Daniel (Zootaxa, 2024)
From the beginning of the 19th century to the present, the authorship of the description of the Balkan wall lizard, Podarcis tauricus (Pallas, 1814) was considered undoubted. Recently, Schmidtler (2022) has been concluded that the description of this species should be attributed to J.G. Georgi. Therefore we have chosen to discuss this issue. The description of Lacerta taurica by Georgi in 1801 was based on earlier works by C.L. Hablitz (1785, 1789). However, his description does not align with our current understanding of the morphological and ecological characteristics of the taxon currently recognized as P. tauricus. Some details contained in this description suggest that it was based not on the species recently known as Podarcis tauricus, but on another lizard inhabiting the same place and recently known as Darevskia lindholmi (Szczerbak, 1962). If recognize authorship of the name Lacerta taurica as belonging to Georgi (1801), this would require transferring that name to the species currently known as D. lindholmi and the need to introduce a new name for the species currently known as P. taurica, that will cause numerous confusions. To provide the stability of the names, we suggest to continue to regard Pallas (1814) as the author of the name Lacerta taurica and will apply to the Commissuion of Zoological Nomenlature for conservation of this status. Regrettably, a specimen collected by Pallas himself in Crimea has not been located until now. However, the search for preserved historic specimens continues.